Pengaruh Fashion Involvement Terhadap Impulse Buying Konsumen Fashion Yang Dimediasi Positive Emotion Di Kota Denpasar - Setiadi, I Made Willy; Warmika, I Gde Ketut (E-Jurnal Manajemen, 2015)
The development of the world of fashion and lifestyle are increasingly accompanied by the increasing number of shopping centers such as department stores, factory outlets, fashion boutiques to make distributions outlet as one of the necessities of life are very important. Fashion on consumer involvement can increase impulsive buying behavior-oriented fashion among those who are accustomed to wearing fashion products. This study aims to determine how fashion influences involvement in mediating the positive emotion towards impulse buying fashion consumers in the city of Denpasar. The sample totaled 119 respondents from all regions of Denpasar with purposive sampling method using path analysis (path analysis). The test results showed that the involvement of fashion influence on impulse buying . In addition, there is an indirect effect of fashion involvement against impulse buying through positive emotion, or in other words the positive emotion is mediating variables.
Keywords: fashion involvement; positive emotion; impulse buying